Education for Europe? Professionalization between effectiveness and autonomy. (November 2018) - Hummrich, Merle
This paper assumes that there has been a discourse shift in the understanding of internationalization from an idealistic view on overcoming national narrow-mindedness to an economic view of effectiveness and self-improvement, which also affects the discourse on Europeanization and building Europe by education. Against this background, the question of which consequences this discourse shift has for education and professionalization, is asked. In the end, two contradictions are pointed out as boundaries of professionalizing European education: the first lies in the opposed understanding of Europe and education for Europe; and the second in the replacement of politics by education (understood not only as bottom up control of political aims by education but also as a specific idea of humanity).